A case report of the enterovirus-D68 associated severe acute respiratory illness in a pediatric case from India - Sumit D. Bhardwaj; Varsha A. Potdar; Pragya D. Yadav; Manohar L. Chaudhary; Mandeep S. Chadha; Devendra Mourya (Elsevier, 2019)
Since, early 2000s, there have been several clusters of enterovirus-D68 (EV D68) associated respiratory illness reported from various countries. Recent largest and most wide-spread outbreak of EV-D68 associated severe acute respiratory illness (SARI) occurred in North America. Present report describes a case of EV-D68 associated severe acute respiratory illness from India with a whole genome sequence. The case was identified through retrospective analysis of Influenza SARI surveillance sample collected during September 2017 using Next Generation sequencing. EV D68 positive child aged two years and presented with asthma like symptoms for which he was admitted to ICU. The child tested negative for Influenza, RSV, Rhinovirus, PIV, hMPV and adenovirus, on real time RT-PCR. And on NGS full EV D68 genome was retrieved belonging to sub-clade B3. In ICU, child received anti-bacterial and anti-viral therapy. The child recovered with-out any sequelae and was discharged one week later. Present report highlights the importance of studying this emergent virus EV-D68 through prospective studies to understand the burden and epidemiological pattern in the country and its implications. Keywords: Enterovirus D68, Genome, India, NGS, Respiratory illness